RESULTS OF SURGICAL TECHNIQUES APPLIED IN BLEPHAROPTOSIS - Ozturk Yucel; Ayyildiz Taha; Ozgur Rodop Ozlen; Oral Yesim; Kocabas Seyhan (Sanamed, 2019)
Objective: Our aim was to analyze the success rates of patients who underwent levator aponeurosis or frontal suspension with silicone tube surgery due to blepharoptosis according to the elevator function (LF) and to compare our results with the literature.